2021
DOI: 10.18632/aging.202817
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin-induced reduction in iron content and PGC-1β expression negatively regulates osteoclast differentiation to play a protective role in postmenopausal osteoporosis

Abstract: As a necessary trace element, iron is involved in many physiological processes. Clinical and basic studies have found that disturbances in iron metabolism, especially iron overload, might lead to bone loss and even be involved in postmenopausal osteoporosis. Hepcidin is a key regulator of iron homeostasis. However, the exact role of hepcidin in bone metabolism and the underlying mechanism remain unknown. In this study, we found that in postmenopausal osteoporosis cohort, the concentration of hepcidin in the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…So far, FPN is the only iron output protein in vertebrates. If the activation of HEP-induced FPN is insufficient or ineffective, iron overload or iron deposition in bones may occur in the body, producing lots of ROS, and ultimately leading to osteoporosis ( 27 ). Jiang et al observed bone loss, bone microstructure damage, bone mineralized area reduction with various density of ferric ammonium citrate (FAC) in OB of zebrafish embryos ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, FPN is the only iron output protein in vertebrates. If the activation of HEP-induced FPN is insufficient or ineffective, iron overload or iron deposition in bones may occur in the body, producing lots of ROS, and ultimately leading to osteoporosis ( 27 ). Jiang et al observed bone loss, bone microstructure damage, bone mineralized area reduction with various density of ferric ammonium citrate (FAC) in OB of zebrafish embryos ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of osteoporosis may be related to the poor regulation of reproductive hormones, calcitonin, growth factors, and various cytokines affecting bone remodeling (Asafo-Adjei et al, 2016). The existing therapeutic methods for osteoporosis mainly include antiresorptive agents and anabolic medications: the previous studies have documented that bisphosphonates and denosumab are the most commonly used antiresorptive therapies (Johnson et al, 2021;Kocjan et al, 2021;Langdahl, 2020); Zhang et al found that hepcidin could protect against osteoporosis by reducing iron level in bone tissues and, in combination with PGC-1β, reduce ROS production and mitochondria, thereby inhibiting osteoclast differentiation and bone resorption (Zhang et al, 2021); additionally, teriparatide and abaloparatide could increase bone mineral density and reduce the risk of fractures (Bernhardsson & Aspenberg, 2018); zoledronic acid and Guilu Erxian Glue could also treat postmenopausal osteoporosis (Si et al, 2020;Xu et al, 2018); despite the certain curative effects, these agents also cause some severe side effects such as inhibition of bone remodeling and increasing the risks of bone necrosis (Asafo-Adjei et al, 2016;Yang et al, 2020). Hence, it could be fruitful to further elucidate the molecular mechanism of osteoporosis and explore novel therapeutic targets.…”
mentioning
confidence: 99%
“…A previous study has shown that the gene expression of PGC-1β in wild-type murine BMMs was higher in RANKL-induced osteoclastogenesis [ 82 ]. Following the over-expression of iron-reducing hormone (Hepcidin), which led to suppression in osteoclast differentiation and bone resorption in BMM isolated from ovariectomized mice, it was found that the level of PGC-1β was low, accompanied with reduced levels of ROS and a lower number of mitochondria in cells [ 83 ]. A reduction in the level of PGC-1β and mitochondrial biogenesis were also observed during the suppression of RANKL-induced osteoclastogenesis and bone resorption following treatment with Cinchonine (CN), an antimalarial drug [ 84 ].…”
Section: Discussionmentioning
confidence: 99%